PQRST (Preview, Question, Read, State and Test) Strategy in Analyzing Students’ Reading Comprehension of Narrative Text Strategi : PQRST (Preview, Question, Read, State and Test) dalam Menganalisis Pemahaman Membaca Siswa pada Teks Narasi - Gladysia Idolani; Dian Novita (Universitas Muhammadiyah Sidoarjo, 2022)
The application of strategy in the learning process can be crucial to support the students’ competence. This study is descriptive - survey research data was obtained from the questionnaire. This study aims to determine the use of the PQRST strategy to improve the reading ability of class XI BHS students at SMAN 1 Porong. The participants in this study were 31 students. In this questionnaire, the researcher gave 10 questions related to learning English, especially in reading and learning after being given the strategy. Based on the questionnaire, it was found that student's like to be taught using the PQRST strategy. It can be seen from the questionnaire question, more student's choose Yes than No and only some students choose sometimes. This is reinforced from the results of the questionnaire that the application of the PQRST strategy is able to help students improve their reading skills and students understand the content of the text from reading.